PENGARUH PROFITABILITAS, LIKUIDITAS DAN LEVERAGE TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR KONSTRUKSI DAN BANGUNAN YANG TERDAFTAR DI BEI PADA MASA PANDEMI - Sembiring, Sabeth; Mahendra, A.; Shalini, Witya; Sinaga, Ria Veronica (UNIKA Santo Thomas, 2023)
The purpose of this study was to obtain empirical evidence that there is an influence between the variables of profitability, liquidity, and leverage on stock prices in Construction and Building Sub-Sector companies listed on the IDX. This type of research is quantitative research. The data used in this research is secondary data. The population in this study includes all construction and building companies listed on the IDX in the 2020-2022 period. The sample in this study were 8 companies that met the criteria. The sampling technique in this study used purposive sampling. The data analysis used to test the hypothesis is multiple regression with a significance level of 5% and by using SPSS version 23.The results of this study indicate that the profitability and liquidity variables have no effect on stock prices, while the leverage variable has a partial effect on stock prices. Profitability, liquidity, and leverage simultaneously affect stock prices.